EPA and DHA acylcarnitines are less cardiotoxic than are saturated and monounsaturated long‐chain acylcarnitines - Liepinsh, Edgars; Gukalova, Baiba; Krims‐Davis, Kristaps; Kuka, Janis; Leduskrasta, Aiga; Korzh, Stanislava; Vilskersts, Reinis; Makrecka‐Kuka, Marina; Konrade, Ilze; Dambrova, Maija (BioFactors (Oxford), 2025)
Elevated levels of fatty acid‐derived long‐chain acylcarnitines are detrimental to cardiac health, primarily because of their adverse effects on mitochondrial function and key metabolic pathways in the heart. While trans‐fatty acids are considered harmful and omega‐3 polyunsaturated fatty acids (PUFAs) are considered beneficial, the specific properties of acylcarnitines derived from these types of fatty acids are not characterized. This study aimed to compare the effects of saturated palmitoylcarnitine (PC), monounsaturated cis‐oleoylcarnitine (cis‐OC), trans‐elaidoylcarnitine (trans‐EC), and polyunsaturated eicosapentaenoylcarnitine (EPAC) and docosahexaenoylcarnitine (DHAC) on heart function, cardiac cell viability, mitochondrial functionality, and insulin signaling pathways. Saturated and monounsaturated acylcarnitines, particularly trans‐EC, significantly reduced cardiac contractility at concentrations of 8–12 μM, and trans‐EC was identified as the most cardiotoxic acylcarnitine. Conversely, the presence of EPAC and DHAC in the perfusion buffer did not impair heart functionality. Saturated and monounsaturated acylcarnitines also drastically reduced H9C2 cell viability and suppressed mitochondrial OXPHOS by up to 70% at 25 μM, whereas PUFA‐derived acylcarnitines caused only a 20%–25% reduction in OXPHOS and did not decrease cell viability. Furthermore, PC, cis‐OC, and trans‐EC significantly inhibited Akt phosphorylation, whereas EPAC and DHAC had a much weaker effect on insulin signaling. In conclusion, saturated and monounsaturated acylcarnitines, particularly trans‐EC, exert significant cardiotoxic effects, primarily through the impairment of cardiac mitochondrial function. The omega‐3 PUFA‐derived acylcarnitines EPAC and DHAC are safe and less likely to damage cardiac mitochondria, cardiac cells, and the heart than other acylcarnitines. PUFA intake might be safer than other long‐chain fatty acid‐containing lipid sources in patients with FAODs and cardiometabolic diseases. Saturated and monounsaturated acylcarnitines, particularly trans‐EC, exert significant cardiotoxic effects, primarily through the impairment of cardiac mitochondrial function. The omega‐3 PUFA‐derived acylcarnitines EPAC and DHAC are safe and less likely to damage cardiac mitochondria, cardiac cells, and the heart than other acylcarnitines.